Analisis Pendapatan Petani Kentang Dengan Dan Tanpa Menerima Manfaat Program Upland di Desa Mokobang Kecamatan Modoinding - Russu, Saskia Tessa Dhea; Waney, Nordy Fritsgerald Lucky; Pangemanan, Paulus Adrian (Sam Ratulangi University, 2023)
This study aims to calculate the consumers of potato farmers with and without receiving the benefits of the dry land program in Mokobang Village, Modoinding District. This research was conducted for 3 months from June to August 2023. This study uses 2 types of data, namely primary and secondary data. Primary data was collected through direct interviews with respondents using a list of questions and secondary data obtained from related institutions and previous studies. Sampling of farmers was carried out purposively (Purposive Sampling), namely sampling occurred in 5 groups of farmer beneficiaries of the highland program, each group of 1 farmer, so that the number of respondents was 5 people and the data to be collected was data from 2021-2023. The data analysis used is an analysis of the impact of the highlands program using the income method with and without receiving the benefits of the highlands program. The results of research and writing show that the income of potato farmers with and without receiving the benefits of the highland program in Mokobang Village, Modoinding District, it can be concluded that the income of potato farmers without receiving the benefits of the highland program is IDR 9,748,925 and with receiving the highland program benefits of IDR 37,119,401. The income of potato farmers in Mokobang Village has increased with receiving the benefits of the highland program.